2019
DOI: 10.1177/0194599819829741
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CD169+ Subcapsular Macrophages during Metastatic Spread of Head and Neck Squamous Cell Carcinoma

Abstract: Objective The purpose of this study is to assess CD169 expression in metastatic and nearby tumor-free lymph nodes of patients with head and neck squamous cell carcinoma (SCC). Study Design Retrospective analysis based on immunohistochemistry. Setting Tertiary care center. Subjects and Methods The abundance of CD169+ cells in the subcapsular sinuses (SCSs) of lymph nodes was assessed immunohistochemically in paraffin-embedded tissue samples derived from 22 patients with oral cavity and oropharyngeal SCC. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In this study, we found ENDOU negative correlates with tumor infiltrating neutrophils, dendritic cells and macrophages, especially M2 macrophages. Macrophages were reported to be involved in HNSCC metastasis (60)(61)(62), chemotherapy (63) and prognosis (64). Macrophages were polarized into M1 and M2 subtypes depending on their environment (65), and were reported to be functionally distinct in cancer (66).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found ENDOU negative correlates with tumor infiltrating neutrophils, dendritic cells and macrophages, especially M2 macrophages. Macrophages were reported to be involved in HNSCC metastasis (60)(61)(62), chemotherapy (63) and prognosis (64). Macrophages were polarized into M1 and M2 subtypes depending on their environment (65), and were reported to be functionally distinct in cancer (66).…”
Section: Discussionmentioning
confidence: 99%
“…PA can increase the cytotoxic activity of T cells and macrophages, thus lowering the risk of metastasis ( 69 ). These modifications are also observed in patients who respond better to ICIs ( 71 73 ). Hence, it seems feasible that PA could act as a potential coadjuvant to immunotherapy, as already observed in pre-clinical models ( 74 ).…”
Section: Discussion and Future Directionsmentioning
confidence: 82%
“…In a study of human head and neck squamous cell carcinoma, it was found that RLN metastasis was related to the density of CD169 + macrophages in the subcapsular sinus of the draining lymph nodes. The number of CD169 + macrophages in patients with lymphatic metastasis is lower than that in patients with lymphatic non-metastasis (101). These results suggest that the density of CD169 + macrophages may be used as a potential indicator for evaluating and detecting the clinical prognosis of malignant tumours.…”
Section: Anti-tumour Roles Of Cd169 + Macrophagesmentioning
confidence: 81%